Metodología para la prestación de sevicios financieros a través de una cooperativa de ahorro y crédito, enfocado en la economía social y solidaria de la parroquia Tambillo perteneciente al cantón Mejía - Franco Bustos, Juan Carlos (2014)
Our project is focused on creating a Cooperative Savings and Credit which benefits the Tambillo Parish, belonging to the Canton Mejía where their main sources of income are agriculture, livestock and micro, where we have proposed an alternative development through of financial intermediation, which benefits the residents of the area, by providing our services and product offerings.